Impacts of the Mesoscale Ocean‐Atmosphere Coupling on the Peru‐Chile Ocean Dynamics: The Current‐Induced Wind Stress Modulation. Issue 2 (1st February 2018) - Oerder, V.; Colas, F.; Echevin, V.; Masson, S.; Lemarié, F.
Abstract: The ocean dynamical responses to the surface current‐wind stress interaction at the oceanic mesoscale are investigated in the South‐East Pacific using a high‐resolution regional ocean‐atmosphere coupled model. Two simulations are compared: one includes the surface current in the wind stress computation while the other does not. In the coastal region, absolute wind velocities are different between the two simulations but the wind stress remains very similar. As a consequence, the mean regional oceanic circulation is almost unchanged. On the contrary, the mesoscale activity is strongly reduced when taking into account the effect of the surface current on the wind stress. This is caused by a weakening of the eddy kinetic energy generation near the coast by the wind work and to intensified offshore eddy damping. We show that, above coherent eddies, the current‐stress interaction generates eddy damping through Ekman pumping and eddy kinetic energy dissipation through wind work. This alters significantly the coherent eddy vertical structures compared with the control simulation, weakening the temperature and vorticity anomalies and increasing strongly the vertical velocity anomalies associated to eddies. Key Points: Including the wind stress/surface current interaction in a mesoscale coupled model reduces significantly the eddy kinetic energy (EKE) The wind work related to this interaction leads to a reduction of the EKE coastal generation and a damping of coherent mesoscale eddies 3‐D structures of cyclonic and anticyclonic coherent eddies are always damped by this resulting negative wind work and large Ekman pumping